2007
DOI: 10.2353/jmoldx.2007.060209
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Promoter Hypermethylation in Hepatocellular Carcinoma by Pyrosequencing of Etiologically Homogeneous Sample Pools

Abstract: Aberrant DNA methylation patterns have been identified in a variety of human diseases, particularly cancer. Pyrosequencing has evolved in recent years as a sensitive and accurate method for the analysis and quantification of the degree of DNA methylation in specific target regions. However, the number of candidate genes that can be analyzed in clinical specimens is often restricted by the limited amount of sample available. Here, we present a novel screening approach that enables the rapid identification of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…17,32,[37][38][39][40][41][42][43][44][45] Genome-wide DNA hypomethylation plays an important role in genomic instability by reactivating transposable DNA sequences and, therefore, contributes to colorectal carcinogenesis. 1,3-6,35,39,46 -48 Previous studies have reported that most carcinomas of colon, stomach, breast, lung, prostate, liver, and esophagus show hypomethylation of LINE-1 compared with matched normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…17,32,[37][38][39][40][41][42][43][44][45] Genome-wide DNA hypomethylation plays an important role in genomic instability by reactivating transposable DNA sequences and, therefore, contributes to colorectal carcinogenesis. 1,3-6,35,39,46 -48 Previous studies have reported that most carcinomas of colon, stomach, breast, lung, prostate, liver, and esophagus show hypomethylation of LINE-1 compared with matched normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It has been already reported that DNMTs are dysregulated in HCC [17][18][19]. To elucidate the possible role of HCV core proteins on the development of HCV-induced HCC, we evaluated the mRNA and protein expression levels of DNMT1 and 3b by qRT-PCR and immunoblot detection in the human hepatoma cell line Huh-7 cells transiently expressing the HCV core protein of different genotypes.…”
Section: Dnmt1 and 3b Expression In Hcv Core Protein Expressing Cellsmentioning
confidence: 99%
“…To date, however, few studies have systematically analyzed the applicability of DNA pooling for the analysis of DNA methylation. Dejeux and colleagues successfully used pyrosequencing to screen DNA methylation across five loci in pooled DNA samples [ 15 ]. However, by pooling samples subsequent to sodium bisulfite treatment, their approach is potentially affected by differential bisulfite conversion biases, and requires relatively large amounts of starting material from each sample.…”
Section: Introductionmentioning
confidence: 99%